2011
DOI: 10.1007/s00464-011-1755-5
|View full text |Cite
|
Sign up to set email alerts
|

First-phase insulin secretion, insulin sensitivity, ghrelin, GLP-1, and PYY changes 72 h after sleeve gastrectomy in obese diabetic patients: the gastric hypothesis

Abstract: Restoration of the first phase of insulin secretion and improved insulin sensitivity in diabetic obese patients immediately after SG, before any food passage through the gastrointestinal tract and before any weight loss, seem to be related to ghrelin, GLP-1, and PYY hormonal changes of possible gastric origin and was neither meal- nor weight-change-related. Duration of the disease up to 10.5 years seems to be a major cut off in the pathophysiological changes induced by SG. A "gastric" hypothesis may be put for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
68
0
8

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(83 citation statements)
references
References 35 publications
7
68
0
8
Order By: Relevance
“…Importantly, in the 75 g oral glucose tolerance tests, the insulinogenic index kept decreasing until the sleeve gastrectomy, and showed a rise after the operation. It has been reported that in diabetic patients, restoration of insulin secretion, improvement of insulin sensitivity and HOMA-R are observed after a sleeve gastrectomy (32,53), and it has also been reported that ghrelin may regulate islet function (54) In the present patient, though insulin resistance was observed, she had not been diagnosed as having diabetes, probably because of excess insulin secretion, and the changes reported in preceding studies were not apparently observed.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Importantly, in the 75 g oral glucose tolerance tests, the insulinogenic index kept decreasing until the sleeve gastrectomy, and showed a rise after the operation. It has been reported that in diabetic patients, restoration of insulin secretion, improvement of insulin sensitivity and HOMA-R are observed after a sleeve gastrectomy (32,53), and it has also been reported that ghrelin may regulate islet function (54) In the present patient, though insulin resistance was observed, she had not been diagnosed as having diabetes, probably because of excess insulin secretion, and the changes reported in preceding studies were not apparently observed.…”
Section: Discussionsupporting
confidence: 48%
“…GIP and GLP-1, a hormone synthesized by the intestinal mucosa in response to food and rapidly inactivated by serine protease dipeptidyl-peptidase (31), has been reported to increase after bariatric surgery (11,32,33). In the present case, though the GLP-1 level measured before the operation is for reference only, the GLP-1 level showed a small elevation, and the GIP levels decreased.…”
Section: Discussionmentioning
confidence: 49%
“…It is known that bariatric surgery can have an acute glycaemic effect: as short as 48 hours after the operation, the patients are known to have improved blood glucose levels 3,23,24,25 . Hence bariatric surgery has been coined as a "surgical treatment for diabetes" 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Basso in his study, reported a "gastric hypothesis" for this restoration of 1st phase insulin secretion, which improves glycemic control. They proposed that decrease in vagally innervated, antral mucosa secretion of gastrin-releasing peptide (GRP) in turn stimulated GLP-1 release [17].…”
Section: Journal Of Obesity and Weight Loss Therapymentioning
confidence: 99%